JENIS KONTRASEPSI HORMONAL DAN LAMA PEMAKAIAN KONTRASEPSI HORMONAL DENGAN KEJADIAN KANKER SERVIKS - Endang Buda Setyowati (Akademi Kebidanan Griya Husada Surabaya, 2017)
Cervical cancer is cancer that grows from cells of the cervix or from cells in the cervix but can grow from the cells of the cervix or both. HPV infection is a major risk factor for cervical cancer. The occurrence of cancer begins with a pre-cancerous condition then leads to advanced cancer. The incidence of cervical cancer at the Yayasan Wisnuwardhana Cancer is still relatively high, with 2.3% of them including hormonal contraception users of 34.84%. This study aims to determine the relationship between the type and duration of hormonal contraceptive use and the incidence of cervical cancer. Method: This study used an analytical method with a cross sectional research design, systematic sampling of random sampling was 324 people. The dependent variable in this study is cervical cancer, while the independent variables are the type of contraception and the duration of use of hormonal contraception. The research instrument is a data collection sheet that takes medical record records. The results of this study were made frequency tables, cross tabulations and then analyzed by the chi square test with the provisions of ? = 0.05 with X2 tables (3.84). Results: The results of the study showed that the majority of mothers who examined the type of pill contraception were 24.2% and the duration of hormonal contraception ? 5 years as many as 16.5% experienced cervical cancer compared to mothers in non-pill contraception as much as 96.4% and in duration of <5 years of hormonal contraception is 92.8% not cervical cancer. After Chi Square test, X2 was calculated (31.89)> X2 table (3.84) in the type of contraception and X2 count (6.66)> X2 table (3.84) in the duration of use of hormonal contraception so that H0 was rejected. Discussion: There is a relationship between the type of hormonal contraception and the duration of use of hormonal contraception with the incidence of cervical cancer. It is recommended that all women while still using pills to perform gynecological examinations regularly, such as pap smears every 6 months to 1 year for early detection of cervical cancer